Growing experience with mTOR inhibitors in pediatric solid organ transplantation - Ganschow, Rainer; Pape, L.; Sturm, E.; Bauer, J.; Melter, M.; Gerner, P.; Höcker, Britta; Ahlenstiel, T.; Kemper, M.; Brinkert, F.; Sachse, M. M.; Tönshoff, Burkhard (Pediatric transplantation, 2013)
Controlled trials of mTOR inhibitors in children following solid organ transplantation are scarce, although evidence from prospective single-arm studies is growing. Everolimus with reduced CNI therapy has been shown to be efficacious and safe in de novo pediatric kidney transplant patients in prospective trials. Prospective and retrospective data in children converted from CNI therapy to mTOR inhibition following kidney, liver, or heart transplantation suggest preservation of immunosuppressive efficacy. Good renal function has been maintained when mTOR inhibitors are used de novo in children following kidney transplantation or after conversion to mTOR inhibition with CNI minimization. mTOR inhibition with reduced CNI exposure is associated with a low risk for developing infection in children. Growth and development do not appear to be impaired during low-dose mTOR inhibition, but more studies are required. No firm conclusions can be drawn as to whether mTOR inhibitors should be discontinued in children requiring surgical intervention or whether mTOR inhibition delays progression of hepatic fibrosis after pediatric liver transplantation. In conclusion, current evidence suggests that use of mTOR inhibitors in children undergoing solid organ transplantation is efficacious and safe, but a number of issues remain unresolved and further studies are required.